Construction project manager's pocket book - Cartlidge, Duncan P. (Routledge pocket books., 2020)
"The second edition of the Construction Project Manager's Pocket Book maintains its coverage of a broad range of project management skills, from technical expertise to leadership, negotiation, team building and communication"--